Efeito do alumínio sobre o balanço iônico e sobre a capacidade das plantas de sorgo para modificar o pH das soluções nutritivas - Cambraia, José; A Trejo Chandías, José; de Moura Estevão, Márcio; Sant'Anna, Renato (Revista Ceres, 2025)
The effect of aluminum on ionic balance and on plant-induced pH changes in the nutrient solution were studied in two cultivars of sorghum: one Al-tolerant (CMSxS-106) and one Al-sensitive (CMSxS-903).